HOW TO TEACH ENGLISH CONVERSATION? AN IMPLEMENTATION OF A MULTIMODAL DISCOURSE ANALYSIS THROUGH IMAGES - Partohap Saut Raja Sihombing; Herman Herman; Nanda Saputra (University of Kuningan, 2022)
The purpose of this research is to identify how is the role of images implementation in teaching English conversation. Rapid technological developments increasingly highlight the use of multimodality theory. Multimodal in this case has a metafunction. Multimodal is now used as a new learning resource that can be used in the learning process. This multimodal aims as an evolving approach to knowledge in visual or image sources. This study used a qualitative descriptive method. In this study, an analysis of multimodal literature is carried out, namely through pictures of English conversations, these images are then used in learning about conversations in English. Three steps of representational metafunction, an interpersonal metafunction, and a compositional metafunction were used to analyze the multimodality of images used as learning media in learning English. The results obtained are that there is an increase in students' understanding when using images as learning media in conversational material in English. Based on the analysis of three multimodal components, namely the representational, interpersonal, and compositional, it is possible to conclude that the image of the English conversation employed leads to adaptation to the qualities of the kid as a learner. Children enjoy animated characters, and the use of color and animation in drawings is designed to pique pupils' interest in participating in learning by displaying images of discussions and encouraging them to practice them.